2017
DOI: 10.1007/s10815-017-0977-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic applications of human anti-Müllerian hormone (AMH) analogues in reproductive medicine

Abstract: Members of the transforming growth factor-beta (TGF-beta) superfamily are key regulators of various physiological processes. Anti-Müllerian hormone (AMH) which is also commonly known as Müllerian-inhibiting substance (MIS) is a member of the TGF-beta superfamily and an important regulator of reproductive organ differentiation and ovarian follicular development. While AMH has been used for diagnostic purposes as a biomarker for over 15 years, new potential therapeutic applications of recombinant human AMH analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 94 publications
(112 reference statements)
1
32
0
Order By: Relevance
“…As such, we explored AMH synthesis in our experimental animals that received stem cell injections, observing a concurrent increase in AMH synthesis. The observation of restored contralateral ovarian function along with the finding of elevated AMH synthesis by the differentiated stem cells, collectively supports the idea that AMH may be important in mediating the observed restoration of ovarian function in these studies [33][34][35][36][37] . Together, these data suggest the feasibility of patients providing their own cells to restore ovarian function, synthesize bioidentical hormones, and restore fertility by neogametogenesis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As such, we explored AMH synthesis in our experimental animals that received stem cell injections, observing a concurrent increase in AMH synthesis. The observation of restored contralateral ovarian function along with the finding of elevated AMH synthesis by the differentiated stem cells, collectively supports the idea that AMH may be important in mediating the observed restoration of ovarian function in these studies [33][34][35][36][37] . Together, these data suggest the feasibility of patients providing their own cells to restore ovarian function, synthesize bioidentical hormones, and restore fertility by neogametogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…The precise paracrine mechanism of action remains elusive for those stem cells, however, AMH proves to be a promising candidate molecule given its preventative effect on follicular atresia and apoptosis 36,37 . AMH is exclusively synthesized by granulosa cells during the early stages of follicular development 38 , and AMH serum concentration is an important measure of ovarian reserve 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The pituitary gland is located outside the blood-brain barrier unlike the hypothalamus (Nussey and Whitehead 2001); therefore, the AMHR2 on gonadotrophs may bind AMH secreted from preantral and small antral follicles. Our data suggested that AMH, like the other TGF-β family members such as inhibin and activin (Kushnir et al 2017), can affect FSH secretion from gonadotrophs. However, little is known about the changes occurring in the blood AMH concentration during the estrous cycle in ruminants (Pfeiffer et al 2014; Koizumi and Kadokawa 2017).…”
Section: Discussionmentioning
confidence: 62%
“…This includes research in better understanding of the genetic and environmental determinants of the AMH levels, molecular signaling pathways, and its interactome. Further, as there is an ongoing research in developing AMH analogues, understanding and examining the effect of any such analogues on non-reproductive systems will also be important 37 .…”
Section: Discussionmentioning
confidence: 99%